Mapping of Risk Levels and Types of Ground Movement in South Sumatra - Saputra, Erlangga; Fathoni, Bulkin; Gofar, Nurly (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
The western part of South Sumatra Province is situated near Bukit Barisan. Therefore, the topography is characterized by hills and mountains. This condition makes the area vulnerable to ground movement. Information on the risk level and type of ground movement is very important for the region's development. This paper presents the mapping of risk level and type of ground movement along the national road system in South Sumatra Province. The map was developed based on slope condition data collected and tabulated in the Slope Management System developed by the Ministry of Public Works based on several parameters. These parameters were processed and analyzed using ArcGIS software. The risk level is classified as low, medium, high, and very high. The type of ground movement is categorized as debris flow, rock fall, slope failure, rock mass failure, embankment failure, rotation failure, and translation failure. The study uses data from 2018 and 2021. Results show that most ground movement on road segments 36, 37, 38, 18, 19, and 21 is slope failure. The map suggests an increase in the number and level of risk of slope failures from 28 in 2018 to 45 in 2021. The map could be used as preliminary information but not as a replacement for slope surveys and investigations.